The Influence of Digital Marketing and Social Media Engagement on Purchase Intention Through Brand Trust Among MSME Consumers - Abdullah Zailani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The rapid advancement of digital technology has significantly transformed the marketing landscape, particularly for Micro, Small, and Medium Enterprises (MSMEs). Digital marketing and social media engagement have become essential strategic tools for businesses seeking to increase consumer awareness, strengthen brand relationships, and stimulate purchasing behavior. Despite the widespread adoption of digital marketing practices, many MSMEs continue to face challenges in converting online engagement into actual purchase intentions. Previous studies have identified brand trust as a critical factor influencing consumer purchasing decisions; however, limited empirical evidence exists regarding its mediating role in the relationship between digital marketing, social media engagement, and purchase intention within the MSME context. This study aims to analyze the influence of digital marketing and social media engagement on purchase intention through brand trust among MSME consumers. A quantitative explanatory research design was employed. Data were collected from 250 consumers who had purchased products from MSMEs through digital platforms. Structural Equation Modeling (SEM-PLS) was used to test the proposed hypotheses. The findings reveal that digital marketing significantly influences brand trust (β = 0.421, p < 0.001), social media engagement significantly affects brand trust (β = 0.387, p < 0.001), and brand trust significantly influences purchase intention (β = 0.551, p < 0.001). Furthermore, brand trust partially mediates the relationship between digital marketing and purchase intention, as well as between social media engagement and purchase intention. The model explains 71.2% of the variance in purchase intention. This study contributes to marketing literature by demonstrating the strategic importance of brand trust as a mechanism through which digital marketing activities influence consumer purchase intentions. The findings provide practical guidance for MSMEs seeking to improve marketing effectiveness in increasingly competitive digital environments.